1992
DOI: 10.1063/1.351652
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission from plastic deformation of a pure single crystal

Abstract: Acoustic emission (AE) during plastic deformation is analyzed for a pure single crystal neglecting the effects of grain boundaries, impurities, and second-phase particles. Acceleration of a moving dislocation is-considered to be the principal AE source. There are two major mechanisms of dislocation motion related to acceleration, initial, and continuous oscillatory motion. Initial motion induced by the creation of mobile dislocations is modeled as a step function of velocity. Continuous oscillatory motion prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Combining nanoindentation and in situ imaging of tested areas [1][2][3][4] enables the evaluation of the initial stages of plastic deformation and fracture. [9][10][11] In most cases both energy-releasing and surface-interaction processes contribute to detected AE signals. Often, there is ambiguity even in highresolution post-test transmission electron microscopy (TEM) images of indented areas.…”
Section: Introductionmentioning
confidence: 99%
“…Combining nanoindentation and in situ imaging of tested areas [1][2][3][4] enables the evaluation of the initial stages of plastic deformation and fracture. [9][10][11] In most cases both energy-releasing and surface-interaction processes contribute to detected AE signals. Often, there is ambiguity even in highresolution post-test transmission electron microscopy (TEM) images of indented areas.…”
Section: Introductionmentioning
confidence: 99%
“…The scratch velocity controls the strain rate of deformation directly and many authors [16,17] have demonstrated that the AE is strongly dependent on strain rate, so the scratch velocity is expected to have a great impact on AE. Furthermore, temperature in the contact region caused by a high scratch velocity is somewhat analogous to strain rate and can influence a material's mechanical responses.…”
Section: Scratch Velocity and Aementioning
confidence: 99%
“…A change in _ can, in principle, be due to a change in m or a change in v [14]. Many experimental results [11,12,15] for AE during tensile testing showed that the mean square voltage (the AE power) of the continuous acoustic emission is proportional to the strain rate, which is expressed by…”
Section: Acoustic Emission During Plastic Deformationmentioning
confidence: 99%